The effectiveness of a school-based intervention to decrease the risk of obesity in primary school children: non-randomized clinical study - CÖBEK ÜNALAN, GÜLRU PEMRA; UZUNER, ARZU (My University, 2022)
Background:The childhood obesity is a growing health problem in our country.There are many intervention studies mostly designed for the management of the overweight and obesechildren, however the childhood obesity necessitates risk assessment and interventions to prevent thedevelopment of obesity.Research questions:What is the risk of obesity among primary school children and the effectiveness of a school based andinteractive intervention planned for risky students and their parents?Method:This is a mixed type design with a cross-sectional study to determine the risk prevalence of obesity followedby a non-randomized controlled study to evaluate the effectiveness of an interactive intervention to decreasethe determined risk.Two different primary schools are selected, one for intervention (IG), the other for the control group (CG);primary year students is the universe. A questionnaire, Food Index (FI) and Family Nutrition and PhysicalActivity tool (FNPA) will be sent to all parents of both schools. The students with fulfilled questionnaires will berecruited in the study, anthropometric measurements will be performed at school. A risk scale defined by theresearchers based on the obesity related questions, BMI, FI and FNPA scores. A total of 165 risky children(55 in IG-110 in CG) will form the sample size. This an eight-weeks and ten-sessions intervention; eight for thestudents only, two for parents, one with all together. The content is designed based on the principles ofhealthy nutrition; the methods will be interactive, including plays and role-plays. A student-parent educationwill be provided to the control group. At the 3rd-6th month following the course measurements and riskquestionnaires will be repeated.Results:Primary outcomes: risk prevalence and the decrease in the risk scores.Conclusions:Our study aims to contribute to primary care by detecting and intervening risky children before obesitydevelops in primary care.Points for discussion:Integration of effective and entertaining child friendly interventions to primary school curriculum could preventchildhood obesity.Presentation on 14/05/2022 15:50 in \"Parallel Session R - One Slide Five Minute Presentations\" by Arzu Uzuner.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Aile Hekimliği; Medicine; Health Sciences; Internal Medicine Sciences; Family Medicine; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Sağlık Politikaları; Aile Sağlığı; Sağlık Bilgi Yönetimi; Temel Bilgi ve Beceriler; Liderlik ve Yönetim; Gözden Geçirme ve Sınav Hazırlığı; Genel Sağlık Meslekleri; Patofizyoloji; Tıbbi Sekreterlik ve Transkripsiyon; Tıbbi Terminoloji; Dahiliye; Değerlendirme ve Teşhis; Tıp (çeşitli); Genel Tıp; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Sağlık Meslekleri (çeşitli); Health Policy; Family Practice; Health Information Management; Fundamentals and Skills; Leadership and Management; Review and Exam Preparation; General Health Professions; Pathophysiology; Medical Assisting and Transcription; Medical Terminology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Community and Home Care; Care Planning; Health Professions (miscellaneous)